Bringing sustainability to life: A framework to guide biodiversity indicator development for business performance management. (14th July 2020) - Addison, Prue F.E.; Stephenson, P. J.; Bull, Joseph W.; Carbone, Giulia; Burgman, Mark; Burgass, Michael J.; Gerber, Leah R.; Howard, Pippa; McCormick, Nadine; McRae, Louise; Reuter, Kim E.; Starkey, Malcolm; et al.
Abstract: Biodiversity loss is a critical sustainability issue, and companies are beginning to seek ways to assess their biodiversity performance. Initiatives to date have developed biodiversity indicators for specific business contexts (e.g., spatial scales—from site, to product, to regional, or corporate scales); however, many are not widely translatable across different contexts making it challenging for businesses seeking indicators to manage their biodiversity performance. By synthesising the steps of common conservation and business decision‐making systems, we propose a framework to support more comprehensive development of quantitative biodiversity indicators, for a range of business contexts. The framework integrates experience from existing tried‐and‐tested conservation frameworks. We illustrate how our framework offers a pathway for businesses to assess their biodiversity performance and demonstrate responsible management by mitigating and reversing their biodiversity impacts and sustaining their dependencies, enabling them to demonstrate their contribution to emerging global biodiversity targets (e.g., Convention on Biological Diversity post‐2020 targets).